2018
DOI: 10.1001/jamapsychiatry.2018.1877
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apathy With Risk of Incident Dementia

Abstract: Apathy was associated with an approximately 2-fold increased risk of dementia in memory clinic patients. Moderate publication bias may have inflated some of these estimates. Apathy deserves more attention as a relevant, cheap, noninvasive, and easily measureable marker of increased risk of incident dementia with high clinical relevance, particularly because these vulnerable patients may forgo health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 70 publications
2
77
3
Order By: Relevance
“…This question is designed to capture anhedonia, and the cross loading observed could reflect different interpretation of this question among respondents because anhedonia is a symptom of depression as well as reflecting apathy, specifically emotional apathy. There is a growing recognition of the importance of the distinction between apathy and depression as markers of dementia (Ismail et al, 2018a;Palmer et al, 2010;Sherman et al, 2018;van Dalen et al, 2018), so it is interesting that there is some loading across both affective and motivation/drive items of the MBI-C. The suggestion here is that, at least in the cognitively normal population, some refinement to the wording of this particular question may be necessary to capture this distinction in the MBI-C. Alternatively, these data raise questions as to whether or not psychiatric constructs developed for a general population, often reflecting neurodevelopmental disorders, accurately represent the emergence of neuropsychiatric symptoms in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This question is designed to capture anhedonia, and the cross loading observed could reflect different interpretation of this question among respondents because anhedonia is a symptom of depression as well as reflecting apathy, specifically emotional apathy. There is a growing recognition of the importance of the distinction between apathy and depression as markers of dementia (Ismail et al, 2018a;Palmer et al, 2010;Sherman et al, 2018;van Dalen et al, 2018), so it is interesting that there is some loading across both affective and motivation/drive items of the MBI-C. The suggestion here is that, at least in the cognitively normal population, some refinement to the wording of this particular question may be necessary to capture this distinction in the MBI-C. Alternatively, these data raise questions as to whether or not psychiatric constructs developed for a general population, often reflecting neurodevelopmental disorders, accurately represent the emergence of neuropsychiatric symptoms in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MCI with apathy have an increased risk of dementia, independent of depression. A systematic review found that apathy was associated with an approximately two-fold increased risk of dementia in memory clinic patients (van Dalen et al, 2018). Robert et al (2006) found that MCI patients with apathy develop AD more than MCI patients without apathy.…”
Section: Apathy: a More Important Indicatormentioning
confidence: 99%
“…8 The presence of apathy significantly affects the patient's and caregivers' quality of life. 11,12 Apathy can be found also in healthy elderly people with subjective cognitive decline (SCD), a condition characterized by self-reported cognitive problems in absence of objective cognitive dysfunction, 13 and in a minor percentage of healthy young adults. 11,12 Apathy can be found also in healthy elderly people with subjective cognitive decline (SCD), a condition characterized by self-reported cognitive problems in absence of objective cognitive dysfunction, 13 and in a minor percentage of healthy young adults.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In people with neurodegenerative disorders, apathy can appear at the early stages of the disease progression, and the presence of apathy can be associated to a faster cognitive and functional decline. 11,12 Apathy can be found also in healthy elderly people with subjective cognitive decline (SCD), a condition characterized by self-reported cognitive problems in absence of objective cognitive dysfunction, 13 and in a minor percentage of healthy young adults. 14 On the basis of the classical apathy definition, 1,15 Robert et al 16 in 2009 proposed a set of diagnostic criteria for apathy (DCA) that patients with brain disorders should meet to receive an apathy diagnosis.…”
Section: Introductionmentioning
confidence: 99%